2018
DOI: 10.1007/s10103-017-2430-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of low-level laser therapy on the healing process of donor site in patients with grade 3 burn ulcer after skin graft surgery (a randomized clinical trial)

Abstract: Skin graft is a standard therapeutic technique in patients with deep ulcers, but managing donor site after grafting is very important. Although several modern dressings are available to enhance the comfort of donor site, using techniques that accelerate wound healing may enhance patient satisfaction. Low-level laser therapy (LLLT) has been used in several medical fields, including healing of diabetic, surgical, and pressure ulcers, but there is not any report of using this method for healing of donor site in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
7

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 22 publications
2
36
0
7
Order By: Relevance
“…Our previous finding showed that LLLT has significant effects on growth factors involved in wound healing, including EGF, FGF, and PDGF, 17 on wound healing, neuropathy, and metabonomics of diabetic patients. 10,18,19 Moreover, its positive effects have been observed in treatment of pressure ulcer, 8 after skin graft surgery, 20,21 and post-cesarean surgery. 22 Several reviews and metaanalyses introduce LLLT as an effective therapeutic modality for wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous finding showed that LLLT has significant effects on growth factors involved in wound healing, including EGF, FGF, and PDGF, 17 on wound healing, neuropathy, and metabonomics of diabetic patients. 10,18,19 Moreover, its positive effects have been observed in treatment of pressure ulcer, 8 after skin graft surgery, 20,21 and post-cesarean surgery. 22 Several reviews and metaanalyses introduce LLLT as an effective therapeutic modality for wound healing.…”
Section: Discussionmentioning
confidence: 99%
“…The role of LLLT for promoting wound healing has long been studied, still there is insufficient literature to design a standard treatment protocol [9][10][11] . Using LLL as an adjunct to conventional treatment of second degree superficial burns is expected to decrease the time of healing, rate of infection, pain and overall cost of treatment.…”
Section: Discussionmentioning
confidence: 99%
“…LPLT is believed to exhibit photochemical, photophysical and photobiological effects, with non-ionizing, polarized, coherent and collimable monochromatic light capable of altering cellular behavior, favoring tissue repair. 1,[3][4][5] It is necessary, for its use, to consider the correct parameters associated with the distance between skin and apparatus, radiated area, type of lenses or mirrors used, type of source, output power, beam divergence emitted, application time, depth of fabric, dispersion, absorption and application technique. 6 In addition, wavelength, pulse type, energy density and frequency of treatment should be considered to provide therapeutic efficacy.…”
Section: Integrative Literature Review Articlementioning
confidence: 99%
“…Porto Alegre, RS, Brazil. Email: ananda.pires@gmail.com ORCID iD: https://orcid.org/0000-0003-4873-2617; 4 Nursing student, Federal University of Rio Grande do Sul / UFRGS. Porto Alegre (RS), Brazil, Email: vitorm@live.com ORCID iD https://orcid.org/0000-0002-3540-7818; 5 PhD, Federal University of Rio Grande do Sul / UFRGS.…”
Section: Introductionmentioning
confidence: 99%